2014
DOI: 10.1063/1.4901348
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-interfaced lab-on-a-chip devices for field-deployable enzyme-linked immunosorbent assay

Abstract: The emerging technologies on mobile-based diagnosis and bioanalytical detection have enabled powerful laboratory assays such as enzyme-linked immunosorbent assay (ELISA) to be conducted in field-use lab-on-a-chip devices. In this paper, we present a low-cost universal serial bus (USB)-interfaced mobile platform to perform microfluidic ELISA operations in detecting the presence and concentrations of BDE-47 (2,2',4,4'-tetrabromodiphenyl ether), an environmental contaminant found in our food supply with adverse h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 59 publications
0
43
0
1
Order By: Relevance
“…Severe air pollution, for example, is linked to respiratory tract infections and chronic obstructive pulmonary disease, and contaminated food and water has often induced diarrheal diseases [65]. A plug-and-play microfluidic ELISA chip was designed to analyze the presence of BDE-47 (2,20,4,40-tetrabromodiphenyl ether) [66]. Studies showed that long-term exposure to BDE-47, a common type of polybrominated diphenyl ethers (PBDEs) as flame retardant in consumer products, significantly deteriorated cognitive function and motor behavior in infants ( Figure 8B) [67].…”
Section: Immunoassaymentioning
confidence: 99%
“…Severe air pollution, for example, is linked to respiratory tract infections and chronic obstructive pulmonary disease, and contaminated food and water has often induced diarrheal diseases [65]. A plug-and-play microfluidic ELISA chip was designed to analyze the presence of BDE-47 (2,20,4,40-tetrabromodiphenyl ether) [66]. Studies showed that long-term exposure to BDE-47, a common type of polybrominated diphenyl ethers (PBDEs) as flame retardant in consumer products, significantly deteriorated cognitive function and motor behavior in infants ( Figure 8B) [67].…”
Section: Immunoassaymentioning
confidence: 99%
“…Another device under development is a low-cost portable smart phone-enabled device to detect the presence and concentrations of the flame retardant BDE-47 (Table 1K). The device uses a lab-on-a-chip (LOC) platform to perform microscale enzyme-linked immunosorbent assays (ELISA) (16).…”
Section: Personal Exposure Monitoringmentioning
confidence: 99%
“…Current applications of MS 2 cover detection of various environmental and health indicators such as pH (Lopez-Ruiz et al 2014), nitrite , heavy metal (Chen et al 2014b;Wang et al 2014), bacterial contamination (Hutchison et al 2015;San Park et al 2013;Zhu et al 2012), blood glucose (Chun et al 2014), proteins (Chan et al 2015;Lillehoj et al 2013;Preechaburana et al 2012;You et al 2013) and other pathogen-associated biomarkers (Fronczek et al 2014;Stemple et al 2014;Yeo et al 2016). Some complicated assays such as enzyme-linked immunosorbent assay (ELISA) (Chen et al 2014a;Wang et al 2011) and polymerase chain reaction (PCR) Liao et al 2016;Stedtfeld et al 2012) were successfully implemented with the MS 2 systems. Furthermore, MS 2 systems offers advantages in test speed, self-containment and sample to result assay operation, which are required for in field test and point of care (PoC) diagnosis (D'Ambrosio et al 2015;Hu et al 2016;Laksanasopin et al 2015;Mudanyali et al 2012).…”
Section: Introductionmentioning
confidence: 99%